The X Formation and its Impact on Tertiary Hydrocarbon Reservoirs in the AX Field, North Iraq - Al-Naemi, Ahmed I.; Mahdi, Arjan M.; Hameed, Ibrahim A. (Journal of Petroleum Research and Studies, 2025)
The study area (AX Field), located in Salah al-Din Governorate, northeast of Tikrit, alongside the structurally higher HY Field, is an area of significant geological interest, particularly concerning its Tertiary hydrocarbon reservoirs. This study aims to delineate the facies of the X Formation and their lateral extensions across drilled wells, focusing on how the increasing number of anhydrite beds impacts the active hydrocarbon reservoir thickness. Data from well logs (AX-ai, bi, ci, di, ei, fi, gi, and HN-hi), formation tops, and final well reports were utilized to construct geological sections, revealing the stratigraphic continuity and variability within the X Formation. Thickness variations were observed, ranging from 19 meters in AX-ei to 51 meters in AX-ji, indicative of a complex depositional environment influenced by tectonic settings, subsidence rates, and sediment supply for sedimentary basin. The primary lithology of the X Formation is characterized by limestone and dolomitic limestone, with significant variations in anhydrite content. Wells such as AX-ei and AX-di have fewer anhydrite layers, whereas AX-ji and HN-hi show substantial evaporitic conditions with multiple anhydrite beds. These lithological variations suggest localized geological factors affecting sedimentation and diagenesis processes. The study concludes that the X Formation is a critical component of the Tertiary reservoir system in the AX Field, serving as both a gas and oil reservoir. The spatial variability in anhydrite lithofacies, increasing northeastward, reflects the complexity of diagenetic processes and sedimentation patterns. Understanding these variations is essential for accurate reservoir characterization and effective hydrocarbon extraction strategies. This research provides valuable insights into the geological and sedimentary dynamics of the AX Field, emphasizing the economic importance thickness and facies of X Formation in the reservoir system.